[Ekslibris] Joh. Due-Nielsen / [Zbigniew Dolatowski]. - Dolatowski, Zbigniew (1927-2001) (1973)
Przedstawia kraba, u dołu napis: Joh. Due-Nielsen. Sygn. aut. w obrębie kompoz., pod wyobrażeniem autograf aut. i data.